Corporate clickbait: the controversial as a visibility tool - Frazon Terra, Carolina (2024)
The text addresses the clickbait strategy at the corporate level. With flashy titles and controversial facts to attract more clicks and increase the reach of visibility of online content, the practice is increasingly common in organizations. Modalities that give visibility to brands are brought to illustrate how the appeal of the unusual attracts the attention of users of social media and the press. It also raises questions about the ethics and quality of content that is produced in this way.